EFEKTIVITAS PENGGUNAAN MEDIA PERIKLANAN PADA UNIVERSITAS DEHASEN BENGKULU (Studi Komparatif Iklan Media Lini Atas dan Iklan Media Lini Bawah) - Vethy Octaviani (Professional: Jurnal Komunikasi dan Administrasi Publik, 2015)
This study aimed to determine the differences between the effectiveness of advertising media on above the line media and below the line media used by Dehasen University Bengkulu as a promotion strategy. Thisis a quantitative survey research. Data was analyzed byusing a different test of Paired Samples T-Test. The effectiveness of advertisements was analyzed by using a descriptive analysis dimension of EPIC (Emphaty, Persuasion, Impact, dan Communication)  Model. The result showed that there are differences in the form of advertising effectiveness of UNIVED Bengkulu presented on above the line media and below the line media in influencing target audience. Emphatically, the advertisement on the top line media was able to utilize the advantages, such as visual excess in newspaper, audio visual in television, and strategic value of banners or billboards. So, persuasively, it’s able to strengthen the characters of the brand as well as foster the perception that UNIVED was identical to personal needs of being able to build awareness, understanding, and action. Meanwhile, advertisement on the bottom line media also proves its effectiveness mainly on media brochures or leaflets which have visual excess and wide space to convey the message. Another media, poster, had the same visual strength as well. However, it cannot assist optimally in associating the advertisement because it did not support the laying image that can affect audience comprehension.